Potential economic impacts - Swallow, B.M. (International Livestock Centre for Africa, 1992)
This paper explores the potential for future economic impacts to arise from the current and future research activities of international agricultural research centres. Special attention is given to the livestock-related research conducted by ILCA. Unfortunately a method for quantifying potential economic impacts has not been well-developed to date. Most analysis have simply applied ex post methods and have thus ignored a fundamental difference between ex post and ex ante analysis: the past is known with certainity while the future is fraught with uncertainities. This section presents a model of potential economic impacts under uncertainity that is appropriate for ex ante analysis. Particular attention is given to the production of knowledge, technique development, technique adoption, policy formulation, research capacity of NARS, flexibility in research strategies, and measures of potential economic impacts. Presents one case study on the value of options created by ILCA's development of the single-ox yoke, harness and plough.